PENGARUH SOSIAL MEDIA MARKETING, BRAND IMAGE, DAN LOKASI TERHADAP MINAT BELI PADA CV. INDO CIPTA KREASI KOTA KEDIRI - Mohammad Gersa Osa Fernanda Arifin; Ahmad Jauhari; Karari Budi Prasasti (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Abstrack The rapid development of technology today really helps society, especially in making it easier to access the desired information and technology via the internet. Social media is one of the factors that greatly influences consumer buying interest, because currently many people are active on the internet so that the dissemination of information about products is easier for consumers to know and reach. This also makes it easier for business people to compete to take advantage of existing opportunities by introducing their products via social media. This research aims to find out about the influence of Social Media Marketing, Brand Image, and Location on Purchase Interest in CV. Indo Cipta Kreasi Kediri City. The analysis techniques used are validity test, reliability test, classical assumptions, multiple linear regression analysis, t test, F test. The population in this study was 200 people and the sample used was 134 respondents using the Slovin method. The results of research on CV. Indo Cipta Kreasi Kediri City shows that the Social Media variable Marketing (X1), Brand Image (X2), and Location (X3) together influence the Purchase Interest variable (Y). This can be proven from the Sig value of 0.000 < 0.05. Keywords: Social Media Marketing; Brand Image; Location